Textual Commentaries to "The Man in the Panther Skin": Who does Rustaveli Refer to as a Witness and Why? - Khintibidze, Elguja (The Kartvelologist - A Bilingual Peer-reviewed, Academic Journal of Georgian Studies, 2016)
The present article comments on one line from the MPS which has often been the subject of discussion in Rustaveli literature: “Dionosi the wise, Ezros bear me witness in this“ („ამ საქმესა მემოწმების დიონოსი, ბრძენი ეზროს“). The idea that Rustaveli refers to the Greek God of love, Eros, as a witness is suggested by the author of the article. The published version of the line is not considered to be the original text, but rather an error introduced by scribes who copied the manuscript over the centuries.